2022
DOI: 10.1186/s43088-022-00279-z
|View full text |Cite
|
Sign up to set email alerts
|

Improved oral bioavailability of poorly water-soluble vorinostat by self-microemulsifying drug delivery system

Abstract: Background Vorinostat is a histone deacetylase inhibitor suberoylanilide hydroxamic acid (SAHA) with anticancer properties. However, it is plagued by low water solubility, low permeability (BCS class IV drug), and suboptimal pharmacokinetics. The purpose of the present study was to develop a self-microemulsifying drug delivery system (SMEDDS) to enhance the oral bioavailability of vorinostat. Capryol 90, labrasol, and polyethylene glycol (PEG 400) were selected as oil phase, surfactant, and co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The UV absorption spectra were measured between wavelengths of 200–400 nm. The maximum absorption wavelength (λ max ) and the spectrum of absorbance against wavelength were recorded [23] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The UV absorption spectra were measured between wavelengths of 200–400 nm. The maximum absorption wavelength (λ max ) and the spectrum of absorbance against wavelength were recorded [23] …”
Section: Methodsmentioning
confidence: 99%
“…The maximum absorption wavelength (λ max ) and the spectrum of absorbance against wavelength were recorded. [23] Fourier transform infrared spectroscopy (FTIR) FTIR Spectrophotometer (Nicolet iS5, Thermo Fisher Scientific, US) was utilized to study the functional groups of ZnO-NPs. The spectrophotometer was set at 20 sample scans, a laser frequency of 15798 cm À 1 and a resolution of 4.0.…”
Section: Ultraviolet-visible Spectroscopymentioning
confidence: 99%
“…Vorinostat-loaded SMEDDS formulation exhibited the significant performance in solubility and bioavailability as compared to Vorinostat-unloaded SMEDDS. The SMEDDS gave a higher absorption rate in GI thanks to opening the tight junctions in the intestine, leading to an increase in intestinal wall permeability [33]. CCL5 nanoparticles did not cause acute toxicity in rats when used at doses higher than 1000 mg/kg.…”
Section: In-vivo Test Of Particles Obtained By Microemulsion Techniquesmentioning
confidence: 98%
“…Ashok Kumar Janakiraman et al reported that the SMEDDS containing capryol 90, PEG 400, and labrasol could remarkably improve the stability and solubility of Vorinostat drug [33]. Vorinostat was dissolved in capryol 90 and mixed with a vortex mixer for 20 minutes to form an oily phase.…”
Section: Sample Vibration (Cmmentioning
confidence: 99%
“…Liquid formulations are prone to stability issues, such as drug degradation, phase separation, and leakage. By converting SMEDDS into solid dosage forms such as powders or pellets, this drug delivery system provides improved stability and convenience in handling, storage, and transportation [7] .  Improved Patient Compliance Solid dosage forms, such as tablets or capsules, are commonly used in oral drug delivery due to their ease of administration and patient acceptance.…”
Section: Requirements Of S-smedds  Enhanced Drug Solubilitymentioning
confidence: 99%